Isolasi Senyawa Polifenol Black garlic Dan Uji Toksisitasnya Terhadap Larva Udang (Artemia salina Leach) - Santi Nur Handayani; Lidya Cahyo Bawono; Diana Pramesti Ayu; Hesti Nurrizqi Pratiwi (Fakultas Farmasi Universitas Pancasila, 2018)
Cancer is one of diseases caused by cell division that is uncontrollable. Cervical cancer is a cancer that suffered by many women. Alternative medicine of cancer disease is use black garlic. Black garlic is the result of processing the garlic with high temperature and humidity without addition of other substances. In that process occur Maillard reaction that cause changes in the color, smell, and taste of the original on the garlic. Such reaction also lead to an increase some bioactive compounds such as S-allyl cysteine ​​(SAC), amino acids, flavonoids, and polyphenols. To determine the toxic properties of black garlic extract, it is necessary to do isolation of polyphenolic compounds and toxicity test against Artemia salina Leach. When calculated by SPSS application, the obtained LC50 values of black garlic extract on the aging prosess time variations of 30 days and 40 days showed concentration of 682.433 and 572.403 ppm.